Zmiana a modele mentalne - Komańda, Marcin (The change and mental models, 2006)
The mental models represent the ideas of the world, forming thoughts and actions. In case of a divergence between the view of the world and the reality, it's possible to understand incorrectly information and to analyze problems in the wrong way. In this case, we have to know the conditions of estimating the planned changes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 369-373